Pengembangan Nutri-Bumil dengan Model APPED Berbasis Website Terintegrasi Chatbot - sapina, Sapina; Mashoedah; Dwi Kurniawan, Prabowo; Arifin, Fatchul; Syaiful Rijal, Bait (Universitas Negeri Gorontalo, 2025)
This study aims to develop the Nutri-Bumil System, a web-based nutrition intake monitoring service for pregnant women integrated with a chatbot. The system development employed a Research and Development (R&D) approach using the APPED model (Analysis, Planning, Production, Evaluation, and Distribution). The research instruments included validation by content experts and media experts using a 4-point Likert scale, which was converted into percentages to assess the system’s feasibility based on the ISO/IEC 25010 software quality standards in the aspects of Usability, Functional Suitability, and Performance Efficiency. The validation results showed that content experts rated the system at 80.71% for Usability, 82.65% for Functional Suitability, and 76.78% for Performance Efficiency, which fall into the categories of Feasible and Fairly Feasible. Meanwhile, media experts provided scores of 80%, 85.41%, and 87.5%, all of which are categorized as Feasible. These findings indicate that the developed Nutri-Bumil system meets the software quality aspects in terms of ease of use, functional suitability, and performance efficiency. Overall, the system is declared Feasible for use as an adaptive, accurate, and efficient digital nutrition service supporting the needs of pregnant women and nutrition professionals.